A survey on AI algorithms applied in communication and computation in Internet of vehicles - Yu KANG; Yaqiong LIU; Tongyu ZHAO; Guochu SHOU (Dianxin kexue)
In the 5G era, the development of communication and computing in the Internet of vehicles has been limited by the rapidly increasing amount of information.New breakthroughs in communication and computing in Internet of vehicles can be achieved by applying AI algorithms to the Internet of vehicles.Firstly, the application of AI algorithms in communication security, communication resource allocation, computation resource allocation, task offloading decision, server deployment, communication-computation integration were investigated.Secondly, the achievements and shortcomings of the present AI algorithms in different scenarios were analyzed.Finally, combined with the Internet of vehicle development trend, some future research directions for AI algorithms applied in the Internet of vehicles were discussed.